DETERMINASI PERTUMBUHAN EKONOMI DI KEPULAUAN RIAU - Rennistia Diah Ayudewi (2022)
Economic growth of a region can be influenced by economic and non-economic factors such as human capital and the role of government. This study aims to determine the effect of HDI, labor, investment, and government spending on economic growth as measured by the value of GDRP in the districts/cities of Riau Islands Province. This study uses a saturated sampling technique in seven (7) regencies/cities during 2015-2021, so the total sample is 49 data obtained from the Central Statistics Agency, the Investment Coordinating Board and other government sources. Panel data analysis in this study combines time series and cross section data. The model chosen is the fixed effect, while the results of the study partially show that HDI, labor , and government spending have a significant effect on economic growth, while investment have no effect on economic growth. The results of the study simultaneously show that HDI, labor, investment, and government spending have an effect on economic growth.